Pengaruh Pembiasaan Shalat Dhuha Terhadap Kedisiplinan Peserta Didik - Jailani, Abdul Kodir; Kustati, Martin; Amelia, Rezki; Gusmirawati; Rosen, Christopher (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2025)
The purpose of this study was to determine the effect of habituation of Dhuha prayer on student discipline at Madrasah Aliyah Negeri (MAN) 3 Mandailing Natal. The type of research conducted is ex-post facto using a quantitative approach. In this study, the population was a total of 766 students. Sampling using Random Sampling technique using the Slovin formula, there were 88 students as samples. The data collection technique uses a questionnaire in the form of a Likert scale, while observation and documentation are as supporting techniques. Based on the results of data processing by testing the research hypothesis using simple linear regression test, obtained sig value. < 0.05 (0.005 < 0.05). Because sig. <0.05 then Ho is rejected and Ha is accepted, meaning that there is a significant influence between habituation of dhuha prayer on student discipline at MAN 3 Mandailing Natal. The R value is 0.300 and the RSquare value is 0.090, meaning that the influence of the independent variable (Dhuha prayer habituation) on the dependent variable (student discipline) is 9%. This research is expected to be able to contribute understanding to the readers that Dhuha prayer is very influential on student discipline. Future research researchers suggest exploring the implementation of Dhuha prayer in the boarding school environment.